Single lens sensor and reference for auto-alignment. (5th March 2018) - Tang, Shun-Xing; Guo, Ya-Jing; Liu, Dai-Zhong; Yang, Lin; Jiang, Xiu-Qing; Peng, Zeng-Yun; Zhu, Bao-Qiang
Abstract : Auto-alignment is a basic technique for high-power laser systems. Special techniques have been developed for laser systems because of their differing structures. This paper describes a new sensor for auto-alignment in a laser system, which can also serve as a reference in certain applications. The authors prove that all of the beam transfer information (position and pointing) can theoretically be monitored and recorded by the sensor. Furthermore, auto-alignment with a single lens sensor is demonstrated on a simple beam line, and the results indicate that effective auto-alignment is achieved.